2022
DOI: 10.1093/nargab/lqac029
|View full text |Cite
|
Sign up to set email alerts
|

High quality genome assembly of the anhydrobiotic midge provides insights on a single chromosome-based emergence of extreme desiccation tolerance

Abstract: Non-biting midges (Chironomidae) are known to inhabit a wide range of environments, and certain species can tolerate extreme conditions, where the rest of insects cannot survive. In particular, the sleeping chironomid Polypedilum vanderplanki is known for the remarkable ability of its larvae to withstand almost complete desiccation by entering a state called anhydrobiosis. Chromosome numbers in chironomids are higher than in other dipterans and this extra genomic resource might facilitate rapid adaptation to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 76 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…The PPP is activated during rehydration of dried P. vanderplanki larvae, leading to synthesis of NADPH, which acts to drive the antioxidant system that alleviates the toxic effects of reactive oxygen species generated during rehydration (64). In Pv11 cells, Treh and Hex were highly expressed during trehalose pretreatment and rehydration (Supplement-Dataset S3) (13). In P. vanderplanki larvae, Treh expression is elevated just before desiccation, but it is not enzymically active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPP is activated during rehydration of dried P. vanderplanki larvae, leading to synthesis of NADPH, which acts to drive the antioxidant system that alleviates the toxic effects of reactive oxygen species generated during rehydration (64). In Pv11 cells, Treh and Hex were highly expressed during trehalose pretreatment and rehydration (Supplement-Dataset S3) (13). In P. vanderplanki larvae, Treh expression is elevated just before desiccation, but it is not enzymically active.…”
Section: Discussionmentioning
confidence: 99%
“…The genome, gene predictions, annotations (accession number GCA_018290095.1) and RNA-Seq data (accession number GSE158443) from our previous study were downloaded from NCBI (13). Gene expression was quantified using RSEM v1.3.1 (--bowtie2) (66) and the following downstream analysis was performed using the Trinity package v2.15.1 (abundance_estimates_to_matrix.pl, run_DE_analysis.pl) (67).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a higher nucleotide diversity, the loss of synteny blocks with other chironomids, and the accumulation of novel gene families was also observed on chromosome 4, highlighting the importance of this chromosome in the evolution of anhydrobiosis in Pol. vanderplanki [ 162 ]. Additionally, a recent preprint described the genome of the anhydrobiotic Pol.…”
Section: Examples Of Genomic Evolution Underlying Anhydrobiosis At Sp...mentioning
confidence: 99%
“…vanderplanki genome shows synteny with the chromosomes of other mosquitoes, this was not the case for the genes on chromosome 4, suggesting extensive genetic turnover and recombination specific to this chromosome. Indeed, gene clustering analysis and annotation showed that numerous novel genes have accumulated on chromosome 4, causing the loss of synteny [ 162 ].…”
Section: Considerations For Future Development In Anhydrobiosis Researchmentioning
confidence: 99%
See 1 more Smart Citation